Efficacy and safety of Saccharomyces boulardii in prevention of antibiotic-associated diarrhoea due to Helicobacter pylori eradication - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2005)
Background and aim Antibiotic-associated diarrhoea may develop during or following Helicobacter pylori eradication. We aimed to evaluate the efficacy and safety of Saccharomyces boulardii in preventing antibiotic-associated diarrhoea in patients receiving antibiotics for H. pylori eradication. Methods In a multicentre prospective clinical trial, patients with peptic ulcer disease or non-ulcer dyspepsia were enrolled to receive clarithromycin, amoxicillin and omeprazole for H. pylori eradication for 14 days. These patients were then randomized to receive either S. boulardii 500 mg twice daily (treatment group) or no treatment (control group). The primary outcome measure was the development of diarrhoea during (treatment period) or within 4 weeks after treatment (follow-up period). Results Of the 389 patients that were enrolled, 376 completed the study. Within the treatment period, diarrhoea developed in 5.9% of patients in the treatment group and in 11.5% of patients in the control group (P = 0.049); and in the follow-up period, diarrhoea developed in 1.0% of patients in the treatment group and in 3.8% of patients in the control group (P = 0.09). Overall diarrhoea rates throughout the whole study period were 6.9% in the treatment group and 15.6% in the control group (P = 0.007). No significant difference was observed between the treatment and control groups in terms of adverse events. Conclusion S. boulardii is an effective and safe treatment for prevention of anti biotic-associated diarrhoea when given concomitantly to patients receiving H. pylori eradication.
Keywords: antibiotic-associated diarrhoea; Helicobacter pylori eradication; Saccharomyces boulardii; CLOSTRIDIUM-DIFFICILE; CLARITHROMYCIN; AMOXICILLIN; INFECTION; THERAPY